2019
DOI: 10.3390/nano9010049
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Wild Enterobacter cloacae Biofilm Formation by Nanostructured Graphene- and Hexagonal Boron Nitride-Coated Surfaces

Abstract: Although biofilm formation is a very effective mechanism to sustain bacterial life, it is detrimental in medical and industrial sectors. Current strategies to control biofilm proliferation are typically based on biocides, which exhibit a negative environmental impact. In the search for environmentally friendly solutions, nanotechnology opens the possibility to control the interaction between biological systems and colonized surfaces by introducing nanostructured coatings that have the potential to affect bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 73 publications
(90 reference statements)
2
20
0
Order By: Relevance
“…However, these approaches are non-specific, which leads to environmental impact resulting from their effect on species not involved in biofilm formation ( Parra et al, 2015a ). While typical approaches rely on the application of coatings with bactericidal payloads, these present limitations such as low durability and gradually lead to bacterial resistance development as well as negative environmental impacts ( Reed et al, 2019 ; Zurob et al, 2019 ). Other control strategies imply the use of polymeric coatings, such as epoxy.…”
Section: Coating Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these approaches are non-specific, which leads to environmental impact resulting from their effect on species not involved in biofilm formation ( Parra et al, 2015a ). While typical approaches rely on the application of coatings with bactericidal payloads, these present limitations such as low durability and gradually lead to bacterial resistance development as well as negative environmental impacts ( Reed et al, 2019 ; Zurob et al, 2019 ). Other control strategies imply the use of polymeric coatings, such as epoxy.…”
Section: Coating Applicationsmentioning
confidence: 99%
“… Parra et al (2015c , 2017) have shown that this mechanism is effective in controlling MIC in Cu and Ni substrates. Zurob et al (2019) studied the effect of graphene and hBN coatings on a wild Gram- Enterobacter cloacae strain biofilm. Graphene-coated glass exhibits 83.6% less biofilm than uncoated glass.…”
Section: Coating Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…E. cloacae is a human opportunistic pathogen that is frequently associated with hospital-acquired infections of the lower respiratory tract, urinary tract, and meninges (Liu et al, 2013). Despite the relevance of E. cloacae as a nosocomial pathogen, its pathogenicity mechanisms are not yet fully understood, but biofilm formation is a virulence feature of this opportunistic microorganism (Zhou et al, 2014;Zurob et al, 2019). In addition, some E. cloacae strains possess cytotoxic activity, suggesting the secretion of bacterial toxins to the cell host (Barnes et al, 1997;Krzyminska et al, 2009).…”
Section: Introductionmentioning
confidence: 99%